DNA Hypomethylation of GR Promoters is Associated with GR Activation and BDNF/AKT/ERK1/2‐Induced Hippocampal Neurogenesis in Mice Derived From Folic‐Acid‐Supplemented Dams. Issue 12 (11th April 2019) - Yang, Yang; Yang, Shu; Liu, Jie; Feng, Yue; Qi, Fulei; Zhao, Ruqian
Abstract : Scope: Glucocorticoid receptor (GR) mediates the nutritional programing of offspring performance. Maternal folic acid has been shown to regulate hippocampal neurogenesis and affect cognitive function in offspring, yet it remains unclear whether and how GR is involved in such effects. Methods and results: Adult male mice derived from dams fed basal or folic‐acid‐supplemented diet (5 mg folic acid/kg) throughout gestation and lactation are used in this study. Maternal folic acid significantly enhances offspring learning and memory with less fear‐related behavior. Concurrently, hippocampal neurogenesis is improved with upregulation of brain‐derived neurotrophic factor and its downstream AKT/ERK1/2 signaling pathway. More GR immune‐positive cells are observed in hippocampus of folic acid group, which are in line with higher GR protein and mRNA abundances. Differential expression of GR exon 1 transcript variants is detected, which is inversely associated with modified DNA methylation on their alternate promoters. Conclusion: The results indicate that maternal folic acid supplementation promotes hippocampal neurogenesis and improves learning and memory behavior in mouse offspring. The mechanisms involve modification of DNA methylation on GR alternate promoters and GR upregulation in the hippocampus, which is associated with activation of BDNF/AKT/ERK1/2 signaling. Abstract : Maternal folate significantly enhances offspring learning and memory with less fear‐related behavior. Hippocampal neurogenesis is improved with upregulation of brain‐derived neurotrophic factor and its downstream AKT/ERK1/2 signaling pathway. Higher GR protein and mRNA abundances are observed in the hippocampus of folate group. Differential expression of GR exon 1 transcript variants is detected, which is inversely correlated with modified DNA methylation on their alternate promoters.